A human kidney and liver organoid‐based multi‐organ‐on‐a‐chip model to study the therapeutic effects and biodistribution of mesenchymal stromal cell‐derived extracellular vesicles - Vivian V. T. Nguyen; Shicheng Ye; Vasiliki Gkouzioti; Monique E. vanWolferen; Fjodor Yousef Yengej; Dennis Melkert; Sofia Siti; Bart deJong; Paul J. Besseling; Bart Spee; Luc J. W. van derLaan; Reyk Horland; et al. (Journal of Extracellular Vesicles, 2022)
Abstract Mesenchymal stromal cell (MSC)‐derived small extracellular vesicles (sEVs) show therapeutic potential in multiple disease models, including kidney injury. Clinical translation of sEVs requires further preclinical and regulatory developments, including elucidation of the biodistribution and mode of action (MoA). Biodistribution can be determined using labelled sEVs in animal models which come with ethical concerns, are time‐consuming and expensive, and may not well represent human physiology. We hypothesised that, based on developments in microfluidics and human organoid technology, in vitro multi‐organ‐on‐a‐chip (MOC) models allow us to study effects of sEVs in modelled human organs like kidney and liver in a semi‐systemic manner. Human kidney‐ and liver organoids combined by microfluidic channels maintained physiological functions, and a kidney injury model was established using hydrogenperoxide. MSC‐sEVs were isolated, and their size, density and potential contamination were analysed. These sEVs stimulated recovery of the renal epithelium after injury. Microscopic analysis shows increased accumulation of PKH67‐labelled sEVs not only in injured kidney cells, but also in the unharmed liver organoids, compared to healthy control conditions. In conclusion, this new MOC model recapitulates therapeutic efficacy and biodistribution of MSC‐sEVs as observed in animal models. Its human background allows for in‐depth analysis of the MoA and identification of potential side effects.